[RETRACTED] BUILDING STUDENTSâ€™ CHARACTER THROUGH MORAL VALUES FROM SUZANNE COLLINâ€™S NOVEL â€œTHE HUNGER GAMESâ€ - Sa’adiyah, Evha Nazalatus (OKARA: Jurnal Bahasa dan Sastra, 2018)
Following careful and considered a review of the article entitled â€œBUILDING STUDENTSâ€™ CHARACTER THROUGH MORAL VALUES FROM SUZANNE COLLINâ€™S NOVEL â€œTHE HUNGER GAMESâ€, Vol. 12, No. 1, Mei 2018 by Evha Nazalatus Saâ€™adiyah. DOI: http://dx.doi.org/10.19105/ojbs.v12i1.1758 The article has been found to be in violation of the Publication principles of OKARA: Jurnal Bahasa dan Sastra, the article contains intentional academic misconduct. The editor investigated and found that the article published in Jurnal al-Hikmah (Jurnal Kependidikan dan Syariah), Volume 5, No. 2, 2017, http://jurnal.staiba.ac.id/index.php/alhikmah/issue/view/7. The author wanted the article to be removed, therefore, the article and its content have been removed from OKARA: Jurnal Bahasa dan Sastra, and reasonable effort should be made to remove all references to this articles.